2020
DOI: 10.1088/1742-6596/1450/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Sprout results characterization of in vitro shoots encapsulation broccoli using sodium alginate

Abstract: One of the in vitro culture techniques to obtain planting material in vitro is through artificial seed technology. The purpose of this research was to obtain a description and test the effects of sodium alginate on in vitro shoot encapsulation in broccoli. Research result for 7 days of storage the highest germination rate of 10 percent in treatment S1 (2 milligram per litre 6- Furfuryl amino purine (KIN)) which was encapsulated with 2 percent sodium alginate (E1). During the 28 days storage the germination rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was concluded that in vitro encapsulation seeds are the product of in vitro shoot encapsulation of broccoli with sodium alginate that germinate effectively through alginate capsules. The seed germination rate increases significantly after storage for up to 28 days, notably with the 2% Na-alginate encapsulation treatment, as compared to other encapsulation treatments [60].…”
Section: Broccoli (Brassica Oleracea Var Italic)mentioning
confidence: 82%
“…It was concluded that in vitro encapsulation seeds are the product of in vitro shoot encapsulation of broccoli with sodium alginate that germinate effectively through alginate capsules. The seed germination rate increases significantly after storage for up to 28 days, notably with the 2% Na-alginate encapsulation treatment, as compared to other encapsulation treatments [60].…”
Section: Broccoli (Brassica Oleracea Var Italic)mentioning
confidence: 82%